El musicante como sujetoterritorio sonoro: un enfoque epistemológico de la experiencia musical. - Jordan Beghelli, Vanessa; Pérez Salazar, Germán Darío (Co-herencia: Revista de Humanidades)
This article proposes a conceptualization of the musicante (the music-making subject) as a "sonic subject-territory," viewing musical experience as a space through which forms of belonging, memory, and knowledge are configured. It argues that sonic territory is not merely a fixed geographical space but a relational, affective, and performative construct that emerges from musical experience, life trajectories, and processes of cultural transmission. From this perspective, the study challenges institutional cartographies of music and the folkloric-essentialist paradigm, which has historically reified musical practices into static identities and cultural hierarchies. In contrast, the article posits the music-making subject as an agent of meaning who constructs territories and resignifies musical practices through situated experience. As its primary contribution, the notion of the "subject-territory" is presented as both an analytical category and an epistemological proposal. This framework invites a rethinking of the legitimation of musical knowledge, opening the discourse toward a plurality of knowledges within the contemporary musical field.